Profile of patients with urinary incontinence treated in the area of urogynecological physiotherapy in a school clinic (Research, Society and Development, 2022)
Objective: To verify the profile of patients with urinary incontinence treated at a teaching clinic. Methodology: This is a descriptive, quantitative and retrospective research. The medical records of patients treated in the area of ​​urogynecological physiotherapy were used in a teaching clinic located in the city of Montes Claros - MG, between January 2017 and July 2022. Results: Fifty medical records of patients aged between 5 and 80 years participated in the study. study, with a predominance of females (84.0%), all with urinary incontinence and with a history of previous urinary infection (90.0%). As causes of urinary leakage, half of the patients reported coughing as the predominant factor, with 50% of the participants reporting that drops was the amount of urine lost. Most patients (80%) did not undergo any type of surgery. Regarding the type of delivery, 90% of the women interviewed underwent normal delivery. The results also show that 100% of the patients were not obese, 90% use medication, 70% do not practice any type of physical activity and 75% had no voluntary contraction. In addition, 10% had pain on vaginal touch and sensitivity was present in 90% of patients. Conclusion: Future work can be developed in order to develop treatment programs and preventive measures that aim to obtain greater efficiency and quality of service provided to patients with this clinical condition.